THE FEES OF MUTUAL FUNDS AND REAL ESTATE FUNDS. THEIR DETERMINANTS IN A SMALL MARKET - ALVES , Paulo (Journal of Advanced Studies in Finance; Vol 6 No 1 (2015): JASF Volume VI, Issue 1(11), Summer, 2015, 2016)
This paper analyses the determinants of expenses from 2007 to 2012 in the Portuguese funds industry. The main contribution is to consider mutual funds and real estate funds simultaneously, particularly the latter, generally created according to customer’s needs, usually for tax reasons. The results confirm the specificity of mutual funds and real estate funds. In the first, expenses are higher on funds composed by shares, derivatives and a large number of assets. In the second, expenses are lower on closed-end funds. In this case, it seems that customers are willing to pay a small fee for tax reasons once their management does not require a special skill. We did not find an evident relationship between expenses and the fund net asset value for both categories of collective schemes. The same occurs between expenses and fund´s performance.